The Effect of Financial Literacy Level and Demographic Factors on Investment Decision - Deavicris Ari Senda; Caecilia Wahyu Estining Rahayu; Christina Heti Tri Rahmawati (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2020)
The aim of this research is to find out the effect of financial literacy level and demographic factors on investment decision on government employees in Kalibawang Community Health Center, Kulon Progo, Yogyakarta. The population of this research is the government employees in Kalibawang Community Health Center, 29 of them are treated as the sample of this research. The sampling technique used in this research is purposive sampling. The respondents are those who have been doing investment. The data used in this research are collected with questionnaires. The data analysis technique used in this research is the Chi Square test. The result shows that financial literacy does not affect investment decision. However, out of the demographic factors, only age, income and investment experience affect investment decision. Meanwhile, the others demograpic factors such as gender and education do not affect investment decision.